2014
DOI: 10.1021/jp5089417
|View full text |Cite
|
Sign up to set email alerts
|

“Building Block Picture” of the Electronic Structure of Aqueous Cysteine Derived from Resonant Inelastic Soft X-ray Scattering

Abstract: The electronic structure of the amino acid L-cysteine in an aqueous environment was studied using resonant inelastic soft X-ray scattering (RIXS) in a 2D map representation and analyzed in the framework of a "building block" approach. The element selectivity of RIXS allows a local investigation of the electronic structure of the three functional groups of cysteine, namely, the carboxyl, amino, and thiol groups, by measuring at the O K, N K, and S L2,3 edges, respectively. Variation of the pH value allows an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 55 publications
4
52
0
Order By: Relevance
“…17 In comparison, only a few publications using XES and RIXS to study amino acids can be found. 9,[25][26][27][28][29] These also include a library of proteinogenic amino acids at all relevant absorption edges 29 and allow for a ''building block picture''. 28 However, to our knowledge, peptides have not been studied with these techniques at all.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 In comparison, only a few publications using XES and RIXS to study amino acids can be found. 9,[25][26][27][28][29] These also include a library of proteinogenic amino acids at all relevant absorption edges 29 and allow for a ''building block picture''. 28 However, to our knowledge, peptides have not been studied with these techniques at all.…”
Section: Introductionmentioning
confidence: 99%
“…9,[25][26][27][28][29] These also include a library of proteinogenic amino acids at all relevant absorption edges 29 and allow for a ''building block picture''. 28 However, to our knowledge, peptides have not been studied with these techniques at all. And while XAS probes the unoccupied electronic states, XES and RIXS also give insights into the occupied valence states, including those directly responsible for the peptide bond.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In aqueous solution, the zwitterionic form is stabilized by hydrogen bonding with water molecules. However, it has been suggested that different chemical states of L-cysteine adsorbed on metallic substrates using aqueous solution are strongly correlated to the pH of the solution during adsorption [38][39][40][41]. Thus, investigations of cysteine-metal bonding using aqueous solutions have revealed complex scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Kamada et al have investigated the ultraviolet photoelectron spectroscopy of solid Cys films, suggesting that the electronic state closest to the valence band maximum should be associated with sulfur based on the photon energy dependence of the ionization cross sections of each constituting atom of Cys. 35 The only two available experimental studies on the electronic property of Cys in the solution phase focused on the core-level structure of Cys, including the sulfur K-edge X-ray absorption near-edge structure spectra of Cys by Risberg et al, 36 and more recently the resonant inelastic soft X-ray scattering study by Meyer et al 37 who probed the oxygen K-, nitrogen K-, and sulfur L 2,3 -edges of Cys at varying pH conditions. These two X-ray based studies agreeably pointed out the significance of the local chemical environment of Cys in affecting their core-level electronic structure.…”
mentioning
confidence: 99%